Effects of lead toxicity on growth and cell wall extensibility in rice seedlings - Hossain, Mohammad Talim; Soga, Kouichi; Wakabayashi, Kazuyuki; Hoson, Takayuki (Bangladesh Journal of Botany, 2018)
The effect of lead (Pb) on growth and mechanical properties of cell wall was investigated in rice seedlings. Caryopses of rice were germinated and grown in various concentrations of lead nitrate for 5 days at 250C in the dark. Growth of rice seedlings was suppressed by Pb ions; significant suppression was caused by low concentration of Pb as 1 μM. Growth suppression was prominent in roots, but not clear in shoot organs, such as coleoptiles or first leaves, suggesting that roots are the primary target of Pb toxicity. The analysis of the cell wall extensibility of rice roots grown in Pb solution indicated that the cell wall extensibility was greatly decreased with increased concentration of Pb ions. These results suggest that Pb may influence the synthesis of cell wall polysaccharides, thereby decreasing the cell wall extensibility, resulting in growth suppression in rice roots.